(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
This article explores the intricate interplay between the biological and psychological significance of emotions in the human experience. Emotions are fundamental to our existence, influencing our interactions with the world and shaping our subjective experiences. From a biological perspective, emotions are deeply rooted in the intricate workings of the brain and the body, directing physiological responses and influencing overall well-being.